2022
DOI: 10.1093/icb/icac002
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Urban Habitats Via Glucocorticoid Regulation: Physiology, Behavior, and Life History in Stream Fishes

Abstract: As environments become urbanized, tolerant species become more prevalent. The physiological, behavioral and life-history mechanisms associated with the success of such species in urbanized habitats are not well understood, especially in freshwater ecosystems. Here we examined the glucocorticoid (GC) profiles, life-history traits, and behavior of two species of fish across a gradient of urbanization to understand coping capacity and associated trade-offs. We studied the tolerant live-bearing Western Mosquitofis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 102 publications
1
7
1
Order By: Relevance
“…Tadpoles from both urban and agricultural habitats had stronger stress response as well as more efficient negative feedback than those in natural habitats. These facets of glucocorticoid regulation are related to fitness in birds and fish [42,52,53], and so is the microbiome in some mammals [83,89]. Yet, here we found no correlation between the corticosterone stress response and negative feedback on the one hand, and bacterial diversity and F/B ratio on the other hand.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Tadpoles from both urban and agricultural habitats had stronger stress response as well as more efficient negative feedback than those in natural habitats. These facets of glucocorticoid regulation are related to fitness in birds and fish [42,52,53], and so is the microbiome in some mammals [83,89]. Yet, here we found no correlation between the corticosterone stress response and negative feedback on the one hand, and bacterial diversity and F/B ratio on the other hand.…”
Section: Discussioncontrasting
confidence: 71%
“…Similar results have been found for other species (red squirrel [32], fish [37]) whereas other studies have found no relationship in unmanipulated populations [38][39][40]. Anthropogenic environments can alter glucocorticoid physiology in wildlife including aquatic vertebrates [41,42], but little is known about the relationship between land use change, associated shifts in host and environmental microbial communities, and stress physiology in the host. Understanding these interactions would provide additional insight into the mechanism associated with tolerance to environmental change.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…It is also possible to link or explore both physiology and behaviour if organisms can be sampled non-invasively and repeatedly, so both can be measured from the same individual. Kolonin et al (2022) found that mosquitofish (Gambusia affinis) showed flexible glucocorticoid profiles that aid in coping with urban streams, but behavioural traits did not vary systematically with urbanisation. Indeed, Lapiedra (2018) indicated that by understanding the mechanistic basis of behavioural variation associated with urbanisation, we could gain a better understanding of how to manage population declines.…”
Section: Using Behavioural Ecology To Explore Adaptive Responses To A...mentioning
confidence: 99%
“…The corticosterone profile illustrates how corticosterone varies in response to stressors. Comprehensive studies of the complete corticosterone profile can aid in understanding how species cope with anthropogenic environmental change (Wingfield, 2013;Sinsch et al, 2020;Bókony et al, 2021;Kolonin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%